Macroeconomic Impact of a Tariff Reduction: A Three-Gap Analysis with Model Simulations - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1997)
Using the interplay of saving, foreign exchange and fiscal constraints, this study determines the impact of trade liberalization, the tariff reduction in particular, on macroeconomic balances. This study then quantifies these effects using a smaller version of the PIDS Annual Macro econometric Model. Results indicate the importance of exchange rate and tax policies.
Keywords: 330; savings gap; foreign exchange gap; fiscal gap